If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.8r = 4r + -16 Reorder the terms: 2.8r = -16 + 4r Solving 2.8r = -16 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 2.8r + -4r = -16 + 4r + -4r Combine like terms: 2.8r + -4r = -1.2r -1.2r = -16 + 4r + -4r Combine like terms: 4r + -4r = 0 -1.2r = -16 + 0 -1.2r = -16 Divide each side by '-1.2'. r = 13.33333333 Simplifying r = 13.33333333
| 4+3y=14 | | 36-9= | | 25y^2-20y+4= | | 3*3-2(3)+1=4 | | 3/5(3x+9)=2(3-2x)+11 | | 15x^2-40x-15=0 | | 8x^2yz+16xy^2z^2-24xyz^2= | | 8x+4=16x | | 18+18= | | 5u+5(1-u)=-3u+8 | | 2b-3=2b-2 | | -4x+9=3x-(1+2x) | | 8(4-3x)=17x+15 | | 2p(p+3)=0 | | -10=3n-5+4 | | 2b-2=2b-2 | | 1/6(x+6)=1/12(2x+12) | | 22y^4-33y^2+11y= | | 3(n+6)=9 | | 3x-3=18+8x | | 6(4x-4)=2(12x+1) | | y(y-6)=0 | | 5y^2=3y-7 | | 2b-3=2b-7 | | 27=p | | -4(6x-2)+3=-24x+11 | | 27=x | | 5-3(-4)=-7 | | 5=3b-8b | | 10.7=-d+43 | | 11x+4=5(2x-1)+9 | | 13-r=-3(-r+1) |